STRATEGI MOBILISASI SUMBER DAYA FUNDAMENTALISME ISLAM: - Arif Gunawan Santoso (Jurnal Dialog, 2015)
Islamic fundamentalist movements are often linked to radicalism and fundamentalism which is identified by the violent and coercion acts. This research portrays the strategy of Hizb ut-Tahrir Indonesia (HTI) as one of the fundamental movement in Indonesia. By using qualitative design as the approach and resource mobilization theory as analysis tool, it is found that HTI does not utilize violence and coercion in their endeavor. Additionally, HTI employs dual approaches in promoting their ideas namely structural political strategy and socio-cultural strategy. Socio-cultural strategies become the main method of HTI in maintaining its existence.